RISK MANAGEMENT ON THE WARSHIP TASK OPERATIONS - Diksono Diksono; Suparno Suparno; Mukhlis Mukhlis (JOURNAL ASRO, 2018)
ABSTRACT The main task of the Indonesia Navy is to enforce the law and maintain security in the territorial sea of national jurisdiction, so that the Indonesian Navy is required to have the main tool of weapons systems (Alutsista) are always ready to carry out the task. The frequent occurrence of accidents experienced by the Indonesian Warship (KRI). This reduces the ability of Warship in performing the task. The purpose of this research is to investigate the causes and effects of accidents, and seek risk mitigation that is considered appropriate. Formal Safety Assessment (FSA) is a structured and systematic methodology used for maritime safety analysis. The fault tree analysis is used to investigate the cause of marine accidents and the event tree analysis is used to determine the impact of an accident. The results of this study are FSA can be effectively applied in accident investigations, although the calculation of cost benefit analysis for warships can be ignored because the Warship task cannot be compared to the value of money. Keywords: Task Operation, Warship, FSA, fault tree analysis, event tree analysis